On the Exact Solutions of Two (3+1)-Dimensional Nonlinear Differential Equations. (22nd June 2020) - Meng, Fanning; Gu, Yongyi
Abstract : In this article, exact solutions of two (3+1)-dimensional nonlinear differential equations are derived by using the complex method. We change the (3+1)-dimensional B-type Kadomtsev-Petviashvili (BKP) equation and generalized shallow water (gSW) equation into the complex differential equations by applying traveling wave transform and show that meromorphic solutions of these complex differential equations belong to class W, and then, we get exact solutions of these two (3+1)-dimensional equations.